Transcriptional Response of Two Brassica napus Cultivars to Short-Term Hypoxia in the Root Zone - Ambros, Stefanie; Kotewitsch, Mona; Wittig, Philipp R.; Bammer, Bettina; Mustroph, Angelika (Frontiers in Plant Science, 2022)
Waterlogging is one major stress for crops and causes multiple problems for plants, for example low gas diffusion, changes in redox potential and accumulation of toxic metabolites. Brassica napus is an important oil crop with high waterlogging sensitivity, which may cause severe yield losses. Its reactions to the stress are not fully understood. In this work the transcriptional response of rapeseed to one aspect of waterlogging, hypoxia in the root zone, was analyzed by RNAseq, including two rapeseed cultivars from different origin, Avatar from Europe and Zhongshuang 9 from Asia. Both cultivars showed a high number of differentially expressed genes in roots after 4 and 24 h of hypoxia. The response included many well-known hypoxia-induced genes such as genes coding for glycolytic and fermentative enzymes, and strongly resembled the hypoxia response of the model organism Arabidopsis thaliana. The carbohydrate status of roots, however, was minimally affected by root hypoxia, with a tendency of carbohydrate accumulation rather than a carbon starvation. Leaves did not respond to the root stress after a 24-h treatment. In agreement with the gene expression data, subsequent experiments with soil waterlogging for up to 14 days revealed no differences in response or tolerance to waterlogging between the two genotypes used in this study. Interestingly, using a 0.1 % starch solution for waterlogging, which caused a lowered soil redox potential, resulted in much stronger effects of the stress treatment than using pure water suggesting a new screening method for rapeseed cultivars in future experiments.